2011
DOI: 10.1002/hbm.21189
|View full text |Cite
|
Sign up to set email alerts
|

Uneven interhemispheric connections between left and right primary sensori‐motor areas

Abstract: To clarify the characteristics of interhemispheric connections, we investigated cortico-cortical evoked potentials (CCEP) in human. Fourteen patients with temporal lobe epilepsy who underwent invasive EEG monitoring with bilaterally implanted subdural electrodes were studied. Electric pulse stimuli were given in a bipolar fashion at two adjacent electrodes on and around the motor area (MA) or sensory area (SA), and CCEP responses were recorded by averaging electrocorticograms from the contralateral hemisphere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…A small positive deflection preceding N1, namely, the onset of N1, is termed P1 by some authors since this could reflect the very first volley to the target cortex [21, 22]. As many CCEP studies have been reported in the last decade, it is now known that CCEP waveform has some variations.…”
Section: Ccep Methodologymentioning
confidence: 99%
“…A small positive deflection preceding N1, namely, the onset of N1, is termed P1 by some authors since this could reflect the very first volley to the target cortex [21, 22]. As many CCEP studies have been reported in the last decade, it is now known that CCEP waveform has some variations.…”
Section: Ccep Methodologymentioning
confidence: 99%
“…We find that using our estimates 252 of volume-weighted average of axon diameter in the numerical simulation leads to callosal 253 delays around 7-25 ms. This range is close to that found in electrophysiological studies 254 (92)(93)(94)(95)(96), and using response-time differences (33,97). For the following sections, we will 255 use an axon diameter of 1.72, 2.81 and 1.3 , for the occipital, motor and frontal tracts, 256…”
Section: Simulation and Choice Of Parameters 197mentioning
confidence: 66%
“…The determinants of conduction velocity of action potential propagation along a myelinated 95 axon have been previously described and modelled. Rushton (18) was the first to describe 96 the dependence of the conduction velocity of a myelinated axon on its geometry.…”
Section: Dependence Of Conduction Velocity On Axon Geometry 94mentioning
confidence: 99%
“…This well-established method allows one to unravel functional connectivity in the cortex [7][8][9][10][11][12] or subcortical regions [13], and recent studies used ECoG-based SPES in humans to investigate CCEPassociated changes in the spectral domain [14,15]. For reviews on studies investigating cortical connectivity by means of CCEPs see [16,17].…”
Section: μEcog Electrode Array Implant and Implantation Proceduresmentioning
confidence: 99%